How do you solve using gaussian elimination or gauss-jordan elimination, X- 3Y + 2Z = -5X3Y+2Z=5, 4X - 11Y + 4Z = -74X11Y+4Z=7, 3X - 8Y + 2Z = -23X8Y+2Z=2?

1 Answer
Sep 26, 2017

The solution is ((X),(Y),(Z))=((34+10Z),(13+4Z),(Z))

Explanation:

Perform the gauss-jordan elimination on the augmented matrix

((1,-3,2,|,-5),(4,-11,4,|,-7),(3,-8,2,|,-2))

We perform the following operations on the rows

R2larrR2-4R1 and R3larrR3-3R1

((1,-3,2,|,-5),(0,1,-4,|,13),(0,1,-4,|,13))

R3larrR3-R2 and R1larrR1+3R2

((1,0,-10,|,34),(0,1,-4,|,13),(0,0,0,|,0))

The solution is

((X),(Y),(Z))=((34+10Z),(13+4Z),(Z))